The history of the controlled marketing of South African deciduous fruit, 1951-1980 - Bestbier, N. A. B.(Nicolaas Andries Blanckenberg) (Stellenbosch : Stellenbosch University, 2012)
Thesis (D. Phil.) -- University of Stellenbosch, 1987.